Cu2 +-CS / Cu-AgNPs colorimetric sensing material as well as preparation method and application thereof
Preparation of CU2+-CS/CU composite materials and nano-silver (AGNPS) through the water heat method to build a color sensing system, solving the problem of complex and high costs in existing technologies, and achieve simple and high costs. Sensitive and practical detection methods.
Patent Information
- Application Number
- CN202411467037.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-21
- Publication Date
- 2025-01-24
AI Technical Summary
The existing aflatoxin B1 detection method has problems such as complex antibody preparation process, long cycle, high cost, easy antibody inactivation, inconvenience of storage and transportation, and cross-reaction, which limits its application in rapid detection.
CU2+-CS/CU composite materials are prepared through the water thermal method, and the color sensor system is constructed in collaboration with nanopal silver (AGNPS) to detect pylorine virin B1.
An aflatoxin B1 detection method with simple operation, high sensitivity and strong practicability has been realized, which can quickly and accurately detect the content of AFB1 and is suitable for the detection of actual samples.
Smart Images

Figure CN119351076A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of preparation of sensing materials, and specifically relates to a Cu 2+ -CS / Cu-AgNPs colorimetric sensing material and its preparation method and application. Background Art
[0002] In the current context of increasing attention paid to global food safety, aflatoxins, as a class of natural toxins widely found in grains, nuts and food processing raw materials, pose a serious threat to human health. Aflatoxins, especially aflatoxin B1 (AFB1), are listed as a Class I carcinogen by the World Health Organization and are closely related to a variety of diseases such as liver cancer. Therefore, the development of rapid, accurate and cost-effective detection methods is crucial to preventing aflatoxin poisoning incidents and ensuring food quality and public health. It is very necessary to develop a simple, portable and visual detection method.
[0003] Common methods for detecting aflatoxin B1 include colorimetric sensing, high performance liquid chromatography (HPLC), enzyme-linked immunosorbent assay (ELISA), colloidal gold method, and fluorescent quantitative detection (PCR). The colloidal gold method is an immunoassay method that uses antibodies as recognition elements. It has the advantages of simple sample pretreatment, easy operation, and fast analysis speed, and is suitable for rapid detection of targets. However, the antibody preparation process is complex, has a long cycle, and is costly. In addition, antibodies are easily inactivated, inconvenient to store and transport, and have cross-reactions. These problems limit the application of immunoassay methods in the rapid detection of AFB1. Therefore, the development of rapid, accurate, and cost-effective detection methods is crucial to preventing aflatoxin poisoning incidents and ensuring food quality and public health. Summary of the invention
[0004] The object of the present invention is to provide a Cu 2+ -CS / Cu-AgNPs colorimetric sensing material and its preparation method and application, Cu was prepared by hydrothermal method 2+ -CS / Cu composite materials, using Cu 2+ -CS / Cu composite material and nano silver (AgNPs) material synergistically construct a colorimetric sensing system for the detection and analysis of AFB1. The detection method established by the present invention has the characteristics of simple operation, high sensitivity and strong practicality, and provides the possibility for the detection of AFB1 in actual samples in the future.
[0005] The present invention is specifically implemented through the following technical solutions. According to a Cu 2+ -CS / Cu-AgNPs colorimetric sensing material, which includes Cu 2+ -CS / Cu composite materials and AgNPs materials, the Cu2+ The preparation method of the CS / Cu composite material comprises the following steps:
[0006] (1.1) Preparation of degradable chitosan:
[0007] A certain amount of iminodiacetic acid, chitosan (CS), and distilled water were added to a round-bottom flask in sequence, stirred at 50°C for 2 hours, and then hydrogen peroxide solution was added. After mixing, the mixture was condensed and refluxed for 3 hours. The degraded chitosan was cooled to room temperature and stored in a refrigerator for later use.
[0008] (1.2) Preparation of Cu 2+ -CS / Cu composite material: Weigh a certain amount of copper sulfate pentahydrate, add a certain amount of degraded chitosan prepared in step (1.1) and a certain amount of anhydrous ethanol to obtain a mixed system, adjust the pH of the mixed system to 8, stir for 30 minutes, place the mixed system in a refrigerator and freeze for 2 hours, then take it out and thaw naturally, repeat the freezing and thawing three times, transfer the obtained mixture to a polytetrafluoroethylene-lined hydrothermal autoclave, perform hydrothermal reaction at 130°C for 24 hours, cool to room temperature after the reaction is completed, filter and collect the product, and dry the product at 60°C for 1 hour to obtain Cu 2+ -CS / Cu composites;
[0009] The preparation method of the AgNPs material comprises:
[0010] (2.1) Add a certain amount of NaBH 4 Dissolve in distilled water to prepare NaBH 4 The solution was then placed in a refrigerator to obtain frozen NaBH 4 ;
[0011] (2.2) Add a certain amount of silver nitrate and sodium citrate to distilled water in sequence, mix and stir for 10 to 20 minutes, and add the frozen NaBH obtained in step (2.1) to the obtained mixed solution. 4 , stir to react, when the color of the mixed system changes from colorless to yellow, continue stirring for 10 to 30 minutes, and then store at 4°C away from light.
[0012] Preferably, in step (1.1), the mass ratio of iminodiacetic acid, chitosan and distilled water is 1:1:40.
[0013] Preferably, the mass fraction of the hydrogen peroxide solution in step (1.1) is 3%.
[0014] Preferably, in step (1.2), the ratio of the mass of copper sulfate pentahydrate to the volume of degraded chitosan and the volume of anhydrous ethanol is: 0.02 (g): 4 (mL): 4 (mL).
[0015] Preferably, in step (2.1), NaBH 4 The concentration of the solution is 0.05 mol / L.
[0016] Preferably, the molar ratio of silver nitrate to sodium citrate in step (2.2) is 1:2, and the added NaBH 4 The molar ratio of silver nitrate is 10:1.
[0017] The present invention also provides a Cu 2+ -CS / Cu-AgNPs colorimetric sensing material is used in the detection of aflatoxin B1. The specific detection method is: 2+ AgNPs material was added to the CS / Cu composite material, and then a certain volume of the test solution containing aflatoxin B1 was added, mixed and allowed to stand for 1 min, and then the mixture was transferred to a quartz cuvette, and the absorbance at 389 nm and 540 nm was detected to calculate A 540 / A 389 , A 540 / A 389 Substitute the linear equation of the standard curve to obtain the concentration of aflatoxin B1 in the test solution.
[0018] Preferably, in the above application, Cu 2+ -The added mass of CS / Cu composite material was 0.0042 g, the added volume of AgNPs material was 2 mL, the added volume of the test solution containing aflatoxin B1 was 1 mL, and the pH value of the test solution containing aflatoxin B1 was adjusted to 4.
[0019] Compared with the prior art, the present invention has obvious advantages and beneficial effects. By means of the above technical solution, the present invention can achieve considerable technical progress and practicality, and has a wide range of utilization value, and has at least the following advantages:
[0020] The present invention prepares Cu by hydrothermal method 2+ -CS / Cu composite materials, Cu 2+ -CS / Cu composite materials and nanosilver (AgNPs) materials work together to construct a colorimetric sensor system that can be used to detect the content of aflatoxin B1. Experiments have shown that only when Cu 2+ -CS / Cu and AgNPs have a significant colorimetric effect on AFB1. When the hydrothermal reaction temperature is 130℃, the prepared Cu 2+ -CS / Cu composite material combined with AgNPs has the best colorimetric effect on AFB1. 2+ -CS / Cu infrared spectrum shows that Cu 2+ Chelates with chitosan molecules to form Cu 2+-CS chelate. Cu 2+ -CS / Cu XRD pattern shows that Cu 2+ -CS / Cu composites contain Cu 2+ -CS chelate and Cu 0 By drawing a standard curve, we obtained the relationship between AFB1 concentration and A 540 / A 389 The linear equation of the present invention is obtained, and the detection conditions are optimized. The colorimetric sensing material preparation method of the present invention is simple, and the quantitative analysis method of AFB1 based on ultraviolet-visible spectrophotometry is simple to operate, highly sensitive, and highly practical, which provides the possibility for the detection of AFB1 in actual samples. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 It is a real picture of the colorimetric system constructed in Examples 8 to 11 in a centrifuge tube.
[0022] Figure 2 It is a graph of absorbance versus wavelength for the colorimetric systems constructed in Examples 8 to 11.
[0023] Figure 3 Example 8 ( Figure 3 (a)), Example 9 ( Figure 3 (b)), Example 10 ( Figure 3 TEM image of the colorimetric system constructed in (c).
[0024] Figure 4 The Cu prepared at different reaction temperatures in Examples 1 to 6 2+ -CS / Cu composites combined with AgNPs for the detection of AFB1 540 / A 389 Comparison chart of values.
[0025] Figure 5 The Cu prepared in Examples 1 to 6 2+ -Infrared spectrum of CS / Cu composite material.
[0026] Figure 6 The Cu prepared in Examples 1 to 6 2+ -XRD pattern of CS / Cu composite.
[0027] Figure 7 It is the UV-visible absorption spectrum of different AgNPs addition amounts in the range of 300 to 700 nm in the colorimetric experiment.
[0028] Figure 8 In the colorimetric experiment, different amounts of AgNPs added to A 540 / A 389 The impact results.
[0029] Fig. 9 In the colorimetric experiment, the AFB1 solution with different pH values has a 540 / A 389 The impact results.
[0030] Fig.10 In the colorimetric experiment, different reaction times affect A 540 / A 389 The impact results. DETAILED DESCRIPTION
[0031] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution of the present invention will be clearly and completely described below in conjunction with specific embodiments. Obviously, the described embodiments are part of the embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0032] The present invention is described in detail with specific examples below. If no specific conditions are specified in the following examples, they are all carried out according to conventional conditions or conditions recommended by the manufacturer. The raw materials and reagents used without specifying the manufacturer are all conventional products that can be purchased from the market.
[0033] The present invention provides a Cu 2+ -CS / Cu-AgNPs colorimetric sensing material, which includes Cu 2+ -CS / Cu composites and silver nanoparticles (AgNPs), Cu 2+ The preparation method of the CS / Cu composite material comprises the following steps:
[0034] (1.1) Preparation of degradable chitosan (CS) polysaccharide:
[0035] Add a certain amount of iminodiacetic acid, chitosan and distilled water into a round-bottom flask in sequence, stir at 50°C for 2 hours, then add 3% hydrogen peroxide solution by mass, mix well and condense and reflux for 3 hours. After the degraded chitosan is cooled to room temperature, store in a refrigerator for later use.
[0036] In this step, the mass ratio of iminodiacetic acid, chitosan and distilled water is 1:1:40.
[0037] (1.2) Preparation of Cu 2+-CS / Cu composite material: Weigh a certain amount of copper sulfate pentahydrate, add a certain amount of degraded chitosan prepared in step (1.1) and a certain amount of anhydrous ethanol to obtain a mixed system, adjust the pH of the mixed system to 8, stir for 30 minutes, place the mixed system in a refrigerator and freeze for 2 hours, then take it out and thaw naturally, repeat the freezing and thawing three times, transfer the obtained mixture to a polytetrafluoroethylene-lined hydrothermal autoclave, perform hydrothermal reaction at 130°C for 24 hours, cool to room temperature after the reaction is completed, filter and collect the product, and dry the product at 60°C for 1 hour to obtain Cu 2+ -CS / Cu composite materials.
[0038] In this step, the ratio of the mass of copper sulfate pentahydrate to the volume of degraded chitosan and the volume of anhydrous ethanol is: 0.02 (g): 4 (mL): 4 (mL).
[0039] The preparation method of the nano silver material comprises:
[0040] (2.1) Add a certain amount of NaBH 4 Dissolve in distilled water to prepare a concentration of 0.05 mol / L NaBH 4 Solution, NaBH 4 The solution was placed in a refrigerator to obtain frozen NaBH 4 ;
[0041] (2.2) Add a certain amount of silver nitrate and sodium citrate to distilled water in sequence, mix and stir for 10 to 20 minutes, and add the frozen NaBH obtained in step (2.1) to the obtained mixed solution. 4 , stirring reaction, when the color of the mixed system changes from colorless to yellow, indicating the formation of nanosilver (AgNPs) colloid, continue stirring for 10 to 30 minutes, and then store at 4°C in the dark. The molar ratio of silver nitrate to sodium citrate is 1:2, and the added NaBH 4 The molar ratio of silver nitrate is 10:1.
[0042] The present invention is described in detail below with specific embodiments:
[0043] Example 1
[0044] Cu 2+ - Preparation of CS / Cu composite materials:
[0045] (1.1) Preparation of degradable chitosan:
[0046] Accurately weigh 1.0g of iminodiacetic acid, 1.0g of chitosan, and 40mL of distilled water, add them into a 100mL round-bottom flask in sequence, stir at 50°C for 2h, then add 1.2mL of 3% hydrogen peroxide solution, mix well and condense and reflux for 3h. The degraded chitosan is light yellow. After cooling to room temperature, store in the refrigerator for later use.
[0047] (1.2) Preparation of Cu 2+ -CS / Cu composite material: Weigh 0.02g of copper sulfate pentahydrate, add 4mL of chitosan degraded in step (1) and 4mL of anhydrous ethanol, adjust the pH of the mixed system to 8, stir for 30min, repeat freeze-thaw three times, transfer the obtained mixture to a polytetrafluoroethylene-lined hydrothermal autoclave, and perform hydrothermal reaction at 130°C for 24h. After the reaction is completed, cool to room temperature, filter and collect the product, and dry the product at 60°C for 1h to obtain Cu 2+ -CS / Cu composite materials.
[0048] Example 2
[0049] The temperature of the hydrothermal reaction in step (1.2) is 70° C., and the rest is the same as in Example 1.
[0050] Example 3
[0051] The temperature of the hydrothermal reaction in step (1.2) is 90° C., and the rest is the same as in Example 1.
[0052] Example 4
[0053] The temperature of the hydrothermal reaction in step (1.2) is 110° C., and the rest is the same as in Example 1.
[0054] Example 5
[0055] The temperature of the hydrothermal reaction in step (1.2) is 150° C., and the rest is the same as in Example 1.
[0056] Example 6
[0057] The temperature of the hydrothermal reaction in step (1.2) is 170° C., and the rest is the same as in Example 1.
[0058] Example 7
[0059] Preparation of silver nanoparticles (AgNPs):
[0060] (2.1) 0.0094 g NaBH 4 Dissolve in 5 mL of distilled water, stir evenly, and freeze to obtain frozen NaBH 4 ;
[0061] (2.2) 0.0042 g of silver nitrate and 0.0147 g of sodium citrate were added to 100 mL of distilled water, mixed and stirred for 10 min, and the frozen NaBH 4 , stir to react, when the color of the mixed system changes from colorless to yellow, it indicates that nanosilver (AgNPs) colloid is formed, continue stirring for 10 minutes, and then store at 4°C away from light.
[0062] Example 8
[0063] Construction of colorimetric system I:
[0064] Add 0.0042 g of Cu prepared in Example 1 into a 5 mL centrifuge tube. 2+ -CS / Cu, then add 2 mL of AgNPs prepared in Example 7, add 1 mL of AFB1 standard solution to the above mixed system to make the final concentration of AFB1 0.3 μg / L, mix well, and form Cu 2+ -CS / Cu-AgNPs-AFB1 system, denoted as colorimetric system I, was transferred to a quartz cuvette, and the UV-visible absorption spectrum was scanned and recorded in the wavelength range of 300-700 nm.
[0065] Example 9
[0066] Construction of colorimetric system II:
[0067] Add 0.0042 g of Cu prepared in Example 1 into a 5 mL centrifuge tube. 2+ -CS / Cu, then add 3 mL of AgNPs prepared in Example 7 and mix well to form Cu 2+ -CS / Cu-AgNPs system, denoted as colorimetric system II, was transferred into a quartz cuvette and the UV-visible absorption spectrum was scanned and recorded in the wavelength range of 300-700 nm.
[0068] Example 10
[0069] Construction of colorimetric system III:
[0070] 3 mL of AgNPs prepared in Example 7 was added to a 5 mL centrifuge tube to form an AgNPs system, recorded as colorimetric system III, which was transferred to a quartz cuvette and the UV-visible absorption spectrum was scanned and recorded in the wavelength range of 300 to 700 nm.
[0071] Embodiment 11
[0072] Construction of colorimetric system IV:
[0073] In a 5 mL centrifuge tube, add 2 mL of the AgNPs prepared in Example 7 and 1 mL of the AFB1 standard solution to make the final concentration of AFB1 0.3 μg / L, mix well to form an AgNPs-AFB1 system, recorded as colorimetric system IV, transfer it to a quartz cuvette, and scan and record the UV-visible absorption spectrum in the wavelength range of 300 to 700 nm.
[0074] The actual photos of the colorimetric system constructed in Examples 8 to 11 in a centrifuge tube are as follows: Figure 1 As shown, the colors of the systems in Examples 9 to 10 are all yellow. The addition of AFB1 in Example 11 makes the color of AgNPs lighter, but the Cu 2+ The color of the -CS / Cu-AgNPs-AFB1 system is reddish brown, indicating that only when Cu 2+ -CS / Cu and AgNPs have a significant colorimetric effect on AFB1.
[0075] The absorbance versus wavelength curves of the colorimetric systems constructed in Examples 8 to 11 are shown in FIG. Figure 2 As shown, Examples 9 to 10 only have strong absorption peaks at 389 nm. In the AgNPs-AFB1 system constructed in Example 11, the original absorption peak of AgNPs at 389 nm slightly decreases and red-shifts, indicating that AFB1 can cause the agglomeration of AgNPs, but the effect is not significant. 2+ -CS / Cu-AgNPs-AFB1 system, the absorption peak at 389nm was significantly weakened, and the absorption peak at 540nm was significantly enhanced, indicating that when AFB1 and Cu 2+ When -CS / Cu-AgNPs were mixed, the agglomeration process of AgNPs increased significantly, the absorption peak at 389nm decreased, and the absorption peak intensity at 540nm increased, indicating that Cu 2+ -CS / Cu and AgNPs jointly promoted the colorimetric detection of AFB1.
[0076] The TEM characterization results of the colorimetric systems constructed in Example 10, Example 9, and Example 8 are as follows: Figure 3 As shown in (a), (b), and (c), from Figure 3 As can be seen from (a), AgNPs have good dispersion and uniform particle size; Figure 3 As can be seen in (b), AgNPs and Cu 2+ -CS@Cu composites are also uniformly dispersed; Figure 3 As can be seen in (c), AgNPs and Cu 2+-CS@Cu aggregated due to the presence of AFB1, indicating that the AgNPs were well dispersed in the absence of AFB1, and with the addition of AFB1, the AgNPs showed obvious aggregation.
[0077] Based on the above characterization results, only in Cu 2+ -CS@Cu and AgNPs work together to produce a significant colorimetric effect on AFB1 ( Figure 1 and Figure 3 ), with the addition of AFB1, the absorbance at 389nm decreased, and a new absorption peak appeared at 540nm ( Figure 2 ), therefore, the subsequent 540 / A 389 As the basis for evaluation, the influence of the hydrothermal reaction temperature on the colorimetric effect in Examples 1 to 7 was investigated.
[0078] According to the method of Example 8, a colorimetric system was constructed, and 6 5 mL centrifuge tubes were prepared, and 0.0042 g of Cu prepared in Examples 1 to 6 was added thereto respectively. 2+ -CS / Cu composite material, and then 2 mL of AgNPs prepared in Example 7 and 1 mL of AFB1 standard solution were added to each centrifuge tube in sequence and mixed evenly to form Cu 2+ -CS / Cu-AgNPs-AFB1 mixed system, the final concentration of AFB1 in the mixed system is 0.3μg / L, the mixed system is transferred to a quartz cuvette, and the absorbance A at 389nm and 540nm is detected 389 and A 540 , calculate A 540 / A 389 , with A 540 / A 389 The hydrothermal reaction temperature of Examples 1 to 6 is plotted as the ordinate and the abscissa, as shown in FIG. Figure 4 As shown in Figure 2, as the reaction temperature increases from 70°C to 130°C, A 540 / A 389 It gradually increases from 0.50 to 0.90; when the reaction temperature rises from 130℃ to 170℃, A 540 / A 389 It can be seen that when the reaction temperature is 130℃, the prepared Cu 2+ -CS / Cu composite material combined with AgNPs has the best colorimetric effect on AFB1.
[0079] The Cu prepared in Examples 1 to 6 was analyzed by Fourier transform infrared spectrometer. 2+ -CS / Cu composite materials were characterized. Figure 5 As shown. At 3000~3500cm -1The absorption peaks in the range are mainly the stretching vibrations of -NH and -OH. The bending vibration absorption peaks of chitosan -NH and -OH are at 1578 cm -1 and 1374cm -1 The Cu prepared at a reaction temperature of 70°C to 170°C 2+ In the -CS / Cu composite material, the absorption peaks corresponding to -NH and -OH gradually decrease or disappear, mainly because Cu 2+ Chelates with chitosan molecules to form chitosan-Cu 2+ Chelate.
[0080] Cu prepared in Examples 1 to 6 2+ -XRD patterns of CS / Cu composites Figure 6 As shown. After comparison with standard Cu 2+ Compared with the portable ID card format card of -CS chelate, the diffraction peaks corresponding to 2θ of 15.1° and 20.8° are similar to those of Cu 2+ The diffraction peaks of the -CS chelate are consistent, which shows that the materials prepared from 70℃ to 170℃ contain Cu 2+ -CS chelate. At the same time, the materials prepared at 130℃, 150℃, and 170℃ have obvious diffraction peaks at 43.3°, 50.4°, and 74.1°, corresponding to Cu 0 The results show that the materials prepared at reaction temperatures of 130℃, 150℃, and 170℃ contain Cu 2+ -CS chelate and Cu 0 Combined with the analysis of the effect of reaction temperature on the colorimetric effect, the Cu prepared at 130°C 2+ -CS / Cu composite material and AgNPs have the best synergistic colorimetric effect on AFB1. It is speculated that the Cu plays a role in the synergistic colorimetric process. 2+ -CS chelate with Cu 0 .
[0081] Cu 2+ -Application of CS / Cu-AgNPs colorimetric sensing materials in the detection of aflatoxin AFB1:
[0082] (1) Preparation of standard curve: Prepare AFB1 standard solutions with concentrations of 0.15 μg / L, 0.3 μg / L, 0.45 μg / L, 0.6 μg / L, and 0.9 μg / L with a pH of 4.0. Prepare four 5 mL centrifuge tubes, and add 0.0042 g of Cu prepared in Example 1 to each centrifuge tube. 2+-CS / Cu composite material and 2mL of AgNPs prepared in Example 7, 1mL of AFB1 standard solution (pH=4.0) was added to four centrifuge tubes respectively to form four mixed systems, the final concentrations of AFB1 in the four mixed systems were 0.05μg / L, 0.1μg / L, 0.15μg / L, 0.2μg / L and 0.3μg / L, respectively, mixed evenly, transferred to a quartz cuvette, and the absorbance at 389nm and 540nm was detected, with A 540 / A 389 The standard curve was drawn with the concentration of AFB1 as the ordinate and the concentration of AFB1 as the abscissa, and the linear equation was obtained: y=2.2839x+0.3015, with a correlation coefficient of 0.9902.
[0083] (2) Optimal dosage of AgNPs: Prepare five 5 mL centrifuge tubes, add 0.0042 g of Cu prepared in Example 1 to each centrifuge tube. 2+ -CS / Cu composite materials, 1.5mL, 2mL, 2.5mL, 3mL, and 3.5mL of the AgNPs prepared in Example 7 were added to each centrifuge tube, and 1mL of the AFB1 standard solution with a pH of 4.0 was added to each tube to form a mixed system, the final concentration of AFB1 in the mixed system was 0.3μg / L, and the mixture was evenly mixed, and the mixture was transferred to a quartz cuvette, and the UV-visible absorption spectrum was scanned and recorded in the wavelength range of 300-700nm, as shown in FIG. Figure 7 As shown. 540 / A 389 The vertical axis is the volume dosage of AgNPs and the horizontal axis is the plotted. Figure 8 shown. Figure 7 and Figure 8 The results show that when the dosage of AgNPs is 1.5mL, the absorbance at 389nm is small, and there is no obvious absorption peak at 540nm; when the dosage of AgNPs is greater than 2mL, the absorbance at 389nm is large, and there is no absorption peak at 540nm. 540 / A 389 When the amount of AgNPs increased from 2mL to 3.5mL, A 540 / A 389 From 0.97 to 0.36. Therefore, Cu 2+ When the -CS / Cu-AgNPs colorimetric sensing material is used to detect aflatoxin AFB1, the optimal dosage of AgNPs is 2mL.
[0084] (3) Optimal pH of AFB1 solution: Prepare seven 5 mL centrifuge tubes, and add 0.0042 g of Cu prepared in Example 1 to each centrifuge tube. 2+-CS / Cu composite material and 2mL of AgNPs prepared in Example 7 were added to seven centrifuge tubes, 1mL of AFB1 solution with pH values of 3, 4, 5, 6, 7, 8, and 9 was added to form a mixed system. The final concentration of AFB1 in the mixed system was 0.3μg / L. The mixture was evenly mixed and transferred to a quartz cuvette. The absorbance at 389nm and 540nm was measured. A 540 / A 389 As the ordinate, the pH of the AFB1 solution is plotted as the abscissa, such as Fig. 9 As shown, as the pH value of AFB1 solution increased from 3 to 4, A 540 / A 389 From 0.73 to 1.01; when the pH value of AFB1 solution increased from 4 to 9, A 540 / A 389 From 1.01 to 0.94. Therefore, Cu 2+ When the -CS / Cu-AgNPs colorimetric sensing material is used to detect aflatoxin AFB1, the pH of the AFB1 solution is preferably adjusted to 4.
[0085] (4) Optimal reaction time: Prepare seven 5 mL centrifuge tubes, and add 0.0042 g of Cu prepared in Example 1 to each centrifuge tube. 2+ -CS / Cu composite material and 2mL of AgNPs prepared in Example 7, 1mL of pH=4 AFB1 solution was added to each of seven centrifuge tubes to form a mixed system, the final concentration of AFB1 in the mixed system was 0.3μg / L, and the mixture was evenly mixed and allowed to stand for 1min, 2min, 5min, 10min, 15min, 30min, and 60min, respectively. After standing, the mixture was transferred to a quartz cuvette, and the absorbance at 389nm and 540nm was detected, with A 540 / A 389 As the vertical axis, the static reaction time is plotted as the horizontal axis, such as Fig.10 The results show that within 60 minutes, A 540 / A 389 The value remains basically unchanged, so the reaction time can be 1min.
[0086] The present invention prepares Cu by hydrothermal method 2+ -CS / Cu composite materials, Cu 2+ -CS / Cu composite materials and silver nanoparticles (AgNPs) work synergistically to construct a colorimetric sensor system. The preparation method of the colorimetric sensing material is simple. The constructed quantitative analysis method of AFB1 based on UV-visible spectrophotometry is simple to operate, highly sensitive, and highly practical, which provides the possibility for the detection of AFB1 in actual samples.
[0087] The above is only an embodiment of the present invention, and does not limit the present invention in any form. The present invention can also have other forms of embodiments according to the above structures and functions, which are not listed one by one. Therefore, any simple modification, equivalent change and modification made by any technician familiar with the profession to the above embodiment according to the technical essence of the present invention without departing from the scope of the technical solution of the present invention still falls within the scope of the technical solution of the present invention.
Claims
1. A Cu 2+ -CS / Cu-AgNPs colorimetric sensing material, characterized in that Including Cu 2+ -CS / Cu composite materials and AgNPs materials, the Cu 2+ The preparation method of the CS / Cu composite material comprises the following steps: (1.1) Preparation of degradable chitosan: A certain amount of iminodiacetic acid, chitosan and distilled water were added to a round-bottom flask in sequence, stirred at 50°C for 2 hours, and then hydrogen peroxide solution was added. After mixing, the mixture was condensed and refluxed for 3 hours. The degraded chitosan was cooled to room temperature and stored in a refrigerator for later use. (1.2) Preparation of Cu 2+ -CS / Cu composite material: weigh a certain amount of copper sulfate pentahydrate, add a certain amount of degraded chitosan prepared in step (1) and a certain amount of anhydrous ethanol to obtain a mixed system, adjust the pH of the mixed system to 8, stir for 30 minutes, place the mixed system in a refrigerator and freeze for 2 hours, then take it out of the refrigerator and thaw naturally, repeat the freezing and thawing three times, transfer the obtained mixture to a polytetrafluoroethylene-lined hydrothermal autoclave, perform hydrothermal reaction at 130°C for 24 hours, cool to room temperature after the reaction is completed, filter and collect the product, and dry the product at 60°C for 1 hour to obtain Cu 2+ -CS / Cu composites; The preparation method of the AgNPs material comprises: (2.1) Dissolve a certain amount of NaBH4 in distilled water to prepare a NaBH4 solution, and then freeze the solution in a refrigerator to obtain frozen NaBH4; (2.2) Add a certain amount of silver nitrate and sodium citrate to distilled water in sequence, mix and stir for 10 to 20 minutes, add the frozen NaBH4 obtained in step (2.1) to the obtained mixed solution, stir and react, when the color of the mixed system changes from colorless to yellow, continue stirring for 10 to 30 minutes, and then store at 4°C away from light.
2. Cu as claimed in claim 1 2+ -CS / Cu-AgNPs colorimetric sensing material, characterized in that In step (1.1), the mass ratio of iminodiacetic acid, chitosan and distilled water is 1:1:
40.
3. Cu as claimed in claim 1 2+ -CS / Cu-AgNPs colorimetric sensing material, characterized in that The mass fraction of the hydrogen peroxide solution in step (1.1) is 3%.
4. Cu as claimed in claim 1 2+ -CS / Cu-AgNPs colorimetric sensing material, characterized in that In step (1.2), the ratio of the mass of copper sulfate pentahydrate to the volume of degraded chitosan and the volume of anhydrous ethanol is 0.02 (g): 4 (mL): 4 (mL).
5. Cu as claimed in claim 1 2+ -CS / Cu-AgNPs colorimetric sensing material, characterized in that The concentration of NaBH4 solution in step (2.1) is 0.05 mol / L.
6. Cu as claimed in claim 1 2+ -CS / CuAgNPs colorimetric sensing material, characterized in that In step (2.2), the molar ratio of silver nitrate to sodium citrate is 1:2, and the molar ratio of added NaBH4 to silver nitrate is 10:
1.
7. The Cu as claimed in claim 1 2+ -CS / Cu-AgNPs colorimetric sensing material is used in the detection of aflatoxin B1.
8. The use according to claim 7, characterized in that At a certain mass of Cu 2+ AgNPs material was added to the CS / Cu composite material, and then a certain volume of the test solution containing aflatoxin B1 was added, mixed and allowed to stand for 1 min, and then the mixture was transferred to a quartz cuvette, and the absorbance at 389 nm and 540 nm was detected to calculate A 540 / A 389 , A 540 / A 389 Substitute the linear equation of the standard curve to obtain the concentration of aflatoxin B1 in the test solution.
9. The use according to claim 8, characterized in that Cu 2+ -The added mass of CS / Cu composite material was 0.0042 g, the added volume of AgNPs material was 2 mL, the added volume of the test solution containing aflatoxin B1 was 1 mL, and the pH value of the test solution containing aflatoxin B1 was adjusted to 4.